Upaya menumbuhkan rasa nasionalisme sejak dini pada anak di era modern - Mulida, Mila Mukaromatul (Maliki Interdisciplinary Journal, 2026)
Instilling a sense of nationalism from an early age is an important foundation in shaping children’s character as the future generation of the nation. In the modern era, marked by rapid technological development and globalization, children are increasingly exposed to foreign cultures that may weaken national identity. This study aims to describe efforts to foster nationalism in early childhood and to identify challenges and strategies that can be implemented within family, school, and community contexts. The research employed a qualitative method using a library research approach by analyzing various scientific sources such as books, national and international journal articles, and relevant educational policy documents. The findings indicate that nationalism can be cultivated through parental and teacher role modeling, integration of national values into learning activities, habituation of national and local cultural practices, and the educational use of